Adenovirus Infection Is Predicted by Prolonged Duration of Diarrhea among Rotavirus-Vaccinated Children below Five Years of Age in Mwanza, Tanzania - Delfina R. Msanga; Tulla S. Masoza; Dina Mahamba; Elizabeth Kwiyolecha; Raphael Rwezaula; Happiness Charles; Regan Kessy; Vitus Silago; Stephan E. Mshana; Mariam M. Mirambo (International Journal of Pediatrics)
Diarrhea is the commonest cause of morbidity and mortality in many resource-limited countries including Tanzania among children below five years of age. A significant number of diarrhea cases associated with severe dehydration are still being reported among children despite five years of rotavirus vaccine implementation in Tanzania necessitating the need to investigate other causes of diarrhea in this population. This study is aimed at determining the prevalence of human adenovirus infection and associated factors among rotavirus-vaccinated children with acute diarrhea in Mwanza, Tanzania. A cross-sectional study was conducted from June to August 2017 involving 137 children less than two years of age admitted with acute diarrhea in the health facilities located in Mwanza, Tanzania. Sociodemographic and other relevant information were collected using standardized rotavirus surveillance tool adopted from WHO. Stool specimens were collected and tested for human adenovirus antigen using immunochromatographic tests. Data were analyzed by using STATA version 13. The median age of enrolled children was 12 (IQR 8-17) months. The prevalence of human adenovirus was found to be 46 (33.6%, 95% CI: 25-41). By multivariable logistic regression analysis, only prolonged duration of diarrhea (OR: 1.619, 95% CI: 1.142-2.295, p=0.007) was found to predict human adenovirus infection among rotavirus-vaccinated children with acute diarrhea. A significant proportion of rotavirus-vaccinated children with prolonged acute diarrhea have adenovirus infection. There is a need to consider other viral pathogens as potential cause of diarrhea especially in this postrotavirus vaccination period.